Efektivitas Asam Asetat dalam Ekstraksi Asam Fitat Pollard - I Hernaman; T Toharmat; W Manalu; P I Pudjiono (Media Peternakan, 2007)
Phytate is commonly high in cereals grain. This compound can be extracted with acid solution. The purpose of this study is to extract phytic acid from pollard using acetic acid at the concentration of 0.1, 0.5, 1, and 5%. Pollard was fractionated using vibrator ball mill to evaluate the distribution of phytic acid in the particle of pollard. One percent of acetic acid was used to extract phytic acid from pollard at ratio of 1:1; 1:1.5; 1:2; and 1:3. The fraction having particle size of 16, 30 and 50 mesh had similar phytic acid content. The results indicated that phytic acid content of these fractions was higher than that of 100 and 400 mesh fractions. Whole pollard had higher phytic acid content than its fractions. Phytic acid in pollard can be extracted by 1% acetic acid solution. Extraction of phytic acid from pollard using 1% acetic acid solution at ratio of 1:3 produced 23.83 g/kg. Key words: extraction, phytic acid, pollard, acetic acid